Access to innovative medicines in Slovenia - Janžič, Andrej (Acta Medico-Biotechnica, 2023)
Reimbursement is acknowledged to be a critical determinant of patient access to innovative medicines, necessitating a balance between accessibility and financial viability. Approximately 35 new innovative medicines and an additional 20 therapeutic indications are assessed from clinical and economical aspects during the reimbursement procedure every year in Slovenia. At the European Union level, ongoing efforts to unify assessment procedures of clinical domains are underway. These initiatives should improve the reimbursement process and ensure timely access to innovative therapies that will be aligned to the evolving needs of healthcare systems across the European Union.